Context-specific adaptation of an eHealth-facilitated, integrated care model and tailoring its implementation strategies—A mixed-methods study as a part of the SMILe implementation science project - Valenta, Sabine; Ribaut, Janette; Leppla, Lynn; Mielke, Juliane; Teynor, Alexandra; Koehly, Katharina; Gerull, Sabine; Grossmann, Florian; Witzig-Brändli, Verena; De Geest, Sabina; , on behalf of the SMILe study team (Frontiers in Health Services, 2023)
Background Contextually adapting complex interventions and tailoring their implementation strategies is key to a successful and sustainable implementation. While reporting guidelines for adaptations and tailoring exist, less is known about how to conduct context-specific adaptations of complex health care interventions. Aims To describe in methodological terms how the merging of contextual analysis results (step 1) with stakeholder involvement, and considering overarching regulations (step 2) informed our adaptation of an Integrated Care Model (ICM) for SteM cell transplantatIon faciLitated by eHealth (SMILe) and the tailoring of its implementation strategies (step 3). Methods Step 1: We used a mixed-methods design at University Hospital Basel, guided by the Basel Approach for coNtextual ANAlysis (BANANA). Step 2: Adaptations of the SMILe-ICM and tailoring of implementation strategies were discussed with an interdisciplinary team (n = 28) by considering setting specific and higher-level regulatory scenarios. Usability tests were conducted with patients (n = 5) and clinicians (n = 4). Step 3: Adaptations were conducted by merging our results from steps 1 and 2 using the Framework for Reporting Adaptations and Modifications–Enhanced (FRAME). We tailored implementation strategies according to the Expert Recommendations for Implementing Change (ERIC) compilation. Results Step 1: Current clinical practice was mostly acute-care-driven. Patients and clinicians valued eHealth-facilitated ICMs to support trustful patient-clinician relationships and the fitting of eHealth components to context-specific needs. Step 2: Based on information from project group meetings, adaptations were necessary on the organizational level (e.g., delivery of self-management information). Regulations informed the tailoring of SMILe-ICM`s visit timepoints and content; data protection management was adapted following Swiss regulations; and steering group meetings supported infrastructure access. The usability tests informed further adaptation of technology components. Step 3: Following FRAME and ERIC, SMILe-ICM and its implementation strategies were contextually adapted and tailored to setting-specific needs. Discussion This study provides a context-driven methodological approach on how to conduct intervention adaptation including the tailoring of its implementation strategies. The revealed meso-, and macro-level differences of the contextual analysis suggest a more targeted approach to enable an in-depth adaptation process. A theory-guided adaptation phase is an important first step and should be sufficiently incorporated and budgeted in implementation science projects.